High Strain Rate Characterization of Shock Absorbing Materials for Landmine Protection Concepts - Jennifer McArthur; Christopher Salisbury; Duane Cronin; Michael Worswick; Kevin Williams (Shock and Vibration)
Numerical modelling of footwear to protect against anti-personnel landmines requires dynamic material properties in the appropriate strain rate regime to accurately simulate material response. Several materials (foamed metals, honeycombs and polymers) are used in existing protective boots, however published data at high strain rates is limited.